2015
DOI: 10.1186/s13104-015-1708-5
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care and women’s decision making power as determinants of institutional delivery in rural area of Western Ethiopia

Abstract: BackgroundDelivery by skilled birth attendance serves as an indicator of progress towards reducing maternal mortality. In Ethiopia, the proportions of births attended by skilled personnel were very low 15 % and Oromia region 14.7 %. The current study identified factors associated with utilization of institutional delivery among married women in rural area of Western Ethiopia.MethodsA community based cross-sectional study was employed from January 2 to January 31, 2015 among mothers who gave birth in the last 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
49
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 25 publications
14
49
3
Order By: Relevance
“…In addition to this, some improvements were made to optimize maternal health care services; for example, ambulance services, portage, “5 to 1” team formation to assist pregnant women to ANC attendance, and coffee ceremonies were arranged by the community around the health institution. On the other hand, reports from Denbia Woreda and Goba district, Ethiopia, showed better uptake than our findings, at 69.7% and 47% (Odo & Shifti, ; Tekelab, Yadecha, & Melka, ), respectively. This discrepancy may be related to cultural differences among the 2 communities.…”
Section: Discussioncontrasting
confidence: 93%
“…In addition to this, some improvements were made to optimize maternal health care services; for example, ambulance services, portage, “5 to 1” team formation to assist pregnant women to ANC attendance, and coffee ceremonies were arranged by the community around the health institution. On the other hand, reports from Denbia Woreda and Goba district, Ethiopia, showed better uptake than our findings, at 69.7% and 47% (Odo & Shifti, ; Tekelab, Yadecha, & Melka, ), respectively. This discrepancy may be related to cultural differences among the 2 communities.…”
Section: Discussioncontrasting
confidence: 93%
“…The finding of this study revealed that 35.3% (95% CI 30.6%, 40.4%) of mothers attended FANC service. This finding was consistent with EDHS 2011 report on Amhara Region 34% [8] and Kenya 32% [9], but was higher than previous studies done in Ethiopia districts like East Wolega 14.4% [10], Dejen and Aneded 12% [11] and abroad Kenya 27% [12]. The difference might be due to cultural and awareness differences and currently the government of Ethiopia has given attention by making the service as one of the exempted services.…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of gender inequities in women's access to reproductive health services between sub-Saharan African and South Asia found that women's abilities to control earnings and influence household decision-making particularly about healthcare are positive predictors for maternal healthcare utilisation [911]. Similar observations have also been made in Ethiopia and Tajikistan on the positive effects of women's decision-making autonomy on their physical mobility [11, 12]. …”
Section: Introductionmentioning
confidence: 75%